Long-Term Follow-up of Individual Therapist Delivered and Standardized Hypnotherapy Recordings in Pediatric Irritable Bowel Syndrome or Functional Abdominal Pain. Issue 1 (4th May 2022) - Rexwinkel, Robyn; Bovendeert, Jeske F.M.; Rutten, Juliette M.T.M.; Frankenhuis, Carla; Benninga, Marc A.; Vlieger, Arine M.
Abstract : Objectives: We previously showed that standardized home-based gut-directed hypnosis exercises with compact disc (CD) is non-inferior to individual hypnotherapy (iHT) by a therapist in the treatment of children with irritable bowel syndrome (IBS) and functional abdominal pain (syndrome) (FAP(S)). Aim of this follow-up study was to investigate the long-term effects of standardized-hypnosis-recordings at home in comparison to iHT. Methods: All participants from our previous randomized controlled trial were invited to complete: 1) an online standardized abdominal pain dairy, on which pain frequency and intensity were scored, and 2) an online questionnaire including adequate relief (AR), anxiety/depression scores, somatization, quality of life (QOL), pain beliefs, school and/or work absenteeism and health care utilization. Results: 227 out of 250 (91%) participants completed this study. After a median duration of 6 years follow-up (5.8-6.2), 80.0% in the CD group vs 86.6% in the iHT group reported AR of their abdominal complaints ( P =.22). Compared to the 1-year follow-up, AR percentages were stable. Treatment success was seen in 67.6% in the CD group vs 71.3% in the iHT group ( P =.66). Anxiety and depression scores, somatization, pain beliefs, health care utilization and school/work absenteeism also improved significantly in both study groups compared with baseline. No differences were found in QOL-scores. Conclusions: Both home-based treatment with standardized-hypnosis-recordings and iHT given by a therapist show persisting positive results in more than 80% of children with IBS and FAP(S) after 6 years of follow-up. These results support the rationale for implementation of this easy-to-use, widely available and cost-effective home-treatment in daily practice.